The Growing Burden of Non-Communicable Diseases in the Eastern Caribbean - World Bank (World Bank, Washington, DC, 2017)
The purpose of this report is to examine and propose options for policy design and implementation, based on a situational analysis for six Eastern Caribbean countries and a review of the lessons of other nations in prevention and control. A committed partner of the Organization of Eastern Caribbean States (OECS) countries, the World Bank is responding to their needs to address the increasing Non-Communicable Diseases (NCDs) burden by providing this report. This report analyzes the situation, reviews lessons learnt in other countries in the prevention and control of major NCDs, and proposes policy options to address the challenges. Specifically, this report aims to provide policy makers with an overview of the NCDs and key risk factors in the region and make inter-country comparisons; assess the economic impact of key NCDs and risk factors where data are available; outline policy options and cost effective interventions for controlling major NCDs that are common to the OECS countries; and provide input for developing a regional health strategy. In the belief that powerful information can drive strategic action, the report aims to: raise awareness of the reality and consequences of failure to take strong action; and identify priority actions that are realistic and tangible for policy makers in developing strategies and allocating resources.